Determination of Student Financial Behavior: The Mediating Effect of Self-Efficacy and Locus of Control - Fitriana Fitriana; Leonardo Davidsi Sipayung; Andhi Febisatria; Zulfahmi Zulfahmi; Aryan Agus Pratama (Public Resource Innovation Management and Excellence, 2026)
This study investigates the effects of financial literacy, digital financial literacy, financial attitudes, and hedonistic lifestyles on financial behavior with self-efficacy and locus of control as mediating variables. The study used qualitative approach with survey design involving 200 students at State University of Makassar. Data was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicated that financial literacy, digital financial literacy, and hedonistic lifestyle significantly influence to self-efficacy. In contrast, financial attitude does not have a statistically significant effect on self-efficacy. Furthermore, financial literacy, digital financial literacy, and financial attitude significantly influence to locus of control, while hedonistic lifestyle does not exert a meaningful influence on this construct. Concerning financial behavior, both of financial literacy and financial attitude show significant direct effect, whereas digital financial literacy and hedonistic lifestyle do not exhibit significant direct relationships. In addition, self-efficacy has a significant effect on financial behavior, while locus of control does not significantly predict this outcome. The mediation analysis indicates that only hedonistic lifestyle has a significant indirect effect on financial behavior through self-efficacy, whereas other indirect effect through self-efficacy and locus of control are not statistically significant. These findings suggest that self-efficacy functions as a more salient psychological mechanism than locus of control in connecting cognitive determinants and lifestyle orientation to financial behavior. This study's will contribute to the theoretical literature by clarifying the differential role of self-efficacy and locus of control. It offers practical implications, emphasizing that improving students’ financial behavior requires strengthening their confidence in financial decision-making and enhancing financial literacy.